Analysis of the Use of Telkomsel and Indosat Providers on the ITP Campus to Improve Internet Signal Quality for Students - Rifqa Durriyatil Ilmi; Sitti Amalia; Andi Syofian (CV. Rayyan Dwi Bharata, 2024)
Walktest is a direct signal quality measurement activity which aims to collect signal parameter data for an operator in a certain area. Usually the walk test is carried out indoors by walking around the area to be measured carrying a walk test device that is equipped with supporting software. Walktest data collection was carried out in several buildings on the ITP campus, namely buildings A, B, C, D, E, and F, where each building consists of 2 floors and 3 floors and the operator whose data will be taken is only for 4G networks, especially Indosat and Telkomsel operators. The parameters to be measured are PCI (Physical Cell Identity) parameters, RSRP (Referenced Signal Receive Power) parameters, RSRQ (Reference Signal Receive Quality) and SINR (Signal to Interference Noise Ratio) parameters. From the results of this walktest, we can find out what the signal quality is in the building and the factors that cause differences in signal quality in the building.